Genetic variation, phylogenetic relationship and spatial distribution of ‘Candidatus Phytoplasma ulmi’ strains in Germany - B. Schneider (Nature Portfolio, 2020)
Abstract A recent survey in Germany revealed the wide presence of ‘Candidatus Phytoplasma ulmi’ in native elm stands. Accessions were studied for their genetic variability and phylogenetic relationship based on the conserved groEL and the variable imp gene. While the groEL sequences revealed a high intraspecific homology of more than 99%, the homology of the imp gene dropped to 71% between distantly related sequences. Twenty-nine groEL and 74 imp genotypes were distinguished based on polymorphic sites. Phylogenetic analysis of the groEL gene clustered all ‘Ca. P. ulmi’ strains and separated them from related phytoplasmas of the 16SrV group. The inferred phylogeny of the imp gene resulted in a different tree topology and separated the ‘Ca. P. ulmi’ genotypes into two clusters, one closely related to the flavescence dorée phytoplasma strain FD-D (16SrV-D), the other affiliated with the flavescence dorée phytoplasma strains FD-C and FD70 and the alder yellows phytoplasma (16SrV-C). In both phylograms, ‘Ca. P. ulmi’ genotypes from Scots elm trees formed a coherent cluster, while genotypes from European white elms and field elms grouped less strictly. The regional distribution pattern was congruent for some of the groEL and imp genotypes, but a strict linkage for all genotypes was not apparent.